Assessing the dynamic tourism inter-industry linkages and economic structural changes in Cambodia's economy - Chantha Hor (Journal of Economic Structures, 2021)
This study employs the SAM-based model combining with multiplier product matrix and field of influence approaches. Under three input-output transaction table matrices of the years 2005, 2010, and 2015, these approaches assess the dynamic tourism inter-industry linkages and structural economic changes in Cambodia. We find that the overall inter-industry connection is relatively low. The textile, other manufacturing, and transportation and communication are key sectors. They have the largest coefficient field of influence of changes in the economic system. Tourism has shifted to be a key sector in 2010 and 2015. However, its backward and forward linkages are still small. It is a relatively promising sector generating a large coefficient field of influence of changes, showing less strength of overall connection with other industries. This study may suggest that there would be a need for promoting, encouraging, and investing in key economic sectors. Policy intervention should focus on developing domestic tourism linkages and strengthening inter-industry ties to diversity tourism benefits the local economy.
Keywords: L16; R15; Z32; 330; Field of influence; Multiplier production matrix model; SAM-based input-output model; Structural changes; Tourism inter-industry linkage